2009
DOI: 10.1038/eye.2009.254
|View full text |Cite
|
Sign up to set email alerts
|

The association between lumican gene polymorphisms and high myopia

Abstract: Purposes Lumican (LUM) is one of the major extracellular matrix components of the sclera. Increasing evidence suggests that changes in the structure and composition of the sclera are major factors in regulating scleral integrity and axial elongation of the eye, as in myopia. Patients and methods Patients (n ¼ 182; age range, 17-24 years) were with a myopic spherical equivalent (SE) 46.5 diopters (D) and the control group comprised individuals (n ¼ 78; age range, 17-25 years) were with a myopic SE o0.5 D. The D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…These studies suggest lumican is a candidate functional gene for high myopia. Indeed, several genetic association studies have reported that lumican polymorphisms contribute to the pathogenesis of high myopia [2,22,23,24,25,26]. However, other studies have suggested lumican polymorphisms are not associated with high myopia [3,6,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies suggest lumican is a candidate functional gene for high myopia. Indeed, several genetic association studies have reported that lumican polymorphisms contribute to the pathogenesis of high myopia [2,22,23,24,25,26]. However, other studies have suggested lumican polymorphisms are not associated with high myopia [3,6,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of myopia varies by country and ethnicity, reaching 70-90% in some Asian populations, 30-40% in Europe and North America, and 10-20% in Africa [1,2]. Simple myopia can be corrected with spectacles or contact lenses, whereas ‘high' (pathological) myopia, typically defined as a refractive error with a spherical equivalent worse than -6 dpt, often predisposes subjects to an increased developmental risk for potentially blinding conditions such as retinal detachment, macular degeneration and glaucoma [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…2,3 We would like to reply to their comments as follows. Myopia is a multigenetic condition involving several overlapping signalling pathways.…”
Section: Reply To Guggenheim Et Almentioning
confidence: 99%
“…They studied four SNPs in 182 highly myopic cases and 78 emmetropic controls, recruited from a sample of 3000 Taiwanese-born medical students aged 16-25 years old (Table 1a). They also published a second study addressing the same question, 2 testing five SNPsFincluding four of those aboveFin 201 high myopes and 86 emmetropic controls, also recruited from 3000 Taiwanese-born volunteers aged 16-25 years old. For the four SNPs common to both studies, the results were similar.…”
mentioning
confidence: 99%
“…2,3 We would like to reply to their comments as follows. Myopia is a multigenetic condition involving several overlapping signalling pathways.…”
Section: Reply To Guggenheim Et Almentioning
confidence: 99%